Influence of Change in Organisational Culture on Performance of Employees in Western Circuit Hotels-Kenya (International Journal of Scientific Research and Management (IJSRM), 2023)
Purpose: The goal of this study was to assess the influence of change in organization culture on performance of employees in western circuit hotels- Kenya. Methodology: To collect and analyze data for this study, correlation research design survey was used together with Lewin’s model and Contingency theories of change for theoretical framework. The target population of this study was 585 staff from different levels from which a sample of 116 was drawn. Stratified random sampling was used with level of staff forming basis of strata. Data instruments were tested for validity via exposure to experts and reliability by Cronbach’s Alpha test on pilot data from 12 respondents. Reliability results indicated all three scales reliable at .801, .777 and .825. Findings: In an aim to identify the influence of change in organization culture on performance of employees within hotels in western tourist circuit Kenya, Regression results showed that change in organization culture had positive influence on employee performance (β=.323) A statistical model accounted for 26.1% of variation in employee performance respectively Contribution to theory and practice: The newly acquired insights in this study will contribute to the literature on change in organization culture and its impact on performance of employees in hotels. In addition, the results could be of help to management and stakeholders in hospitality industry being a major employer in the country, students pursuing course in hospitality, improving employee performance, loyalty and attitude towards work to realize great overall performance. The study recommends that the organizations become vigilant on activities of culture change.